Diasporic Music in Transition: Turkish Immigrant Performers on the Stage of Multikulti Berlin - (:unkn) unknown (TAYLOR & FRANCIS LTD, 2014)
This article examines the dynamics of music production by German-Turkish youth in Berlin. Taking into consideration the changes that globalism has wrought on the conditions and form of migration, the study investigates how interaction between cultures is transforming the ways in which new generations of Turkish immigrants produce music. It identifies the emergence of Turkish youth within Berlin's multicultural music scene, especially in the 2000s, and documents the rise of electronic and rock music production in addition to the more oft studied hip hop and homeland-oriented, traditional forms of music. In comparison with the tone of the music of older immigrant generations, which evoked a tenacious, diasporic spirit, the music of younger generations is more flexible, open and integrated and accommodates rather than rejects differences.